Popularizing anthropology - MacClancy, Jeremy; McDonaugh, Chris 1953- (Routledge, 1996)
Anthropology written for a popular audience is the most neglected branch of the discipline.Popularizing Anthropology unearths a submerged tradition within anthropology and reveals that, from the beginning, anthropologists have looked beyond the boundaries of the academy for their listeners. It aims to establish the popularization of the discipline as an illuminating topic of investigation in its own right, arguing that it is not an irrelevant appendage to the main body of the subject but has always been an integral part of it.